Suitable binder for Li-ion battery anode produced from rice husk - Seiji Kumagai (Nature Portfolio, 2021)
Abstract Rice husk (RH) is a globally abundant and sustainable bioresource composed of lignocellulose and inorganic components, the majority of which consist of silicon oxides (approximately 20% w/w in dried RH). In this work, a RH-derived C/SiOx composite (RHC) was prepared by carbonization at 1000 °C for use in Li-ion battery anodes. To find a suitable binder for RHC, the RHC-based electrodes were fabricated using two different contemporary aqueous binders: polyacrylic acid (PAA) and a combination of carboxymethyl cellulose and styrene butadiene rubber (CMC/SBR). The rate and cycling performances of the RHC electrodes with respect to the insertion/extraction of Li ions were evaluated in a half-cell configuration. The cell was shorted for 24 h to completely lithiate the RHC. Impedance analysis was conducted to identify the source of the increase in the resistance of the RHC electrodes. The RHC electrode fabricated using PAA exhibited higher specific capacity for Li-ion extraction during the cycling test. The PAA binder strengthened the electrode and alleviated the increase in electrode resistance caused by the formation of the interphase film. The high affinity of PAA for SiOx in RHC was responsible for the stabilization of the anodic performance of Li-ion batteries.